Penerapan Sistem Informasi Pembayaran SPP Siswa SMA Swasta Manda Elu Berbasis Web - Katrina Peda Daido; Stefanus Dwi Istiavan Mau; Emirensiana Dappa Ege (Asosiasi Profesi Telekomunikasi Dan Informatika Indonesia, 2025)
This research, entitled “Implementation of a Web-Based Student Tuition Payment Information System at SMA Swasta Manda Elu,” aims to improve the efficiency of recording and managing students’ tuition fee payments. Previously, the tuition payment process was handled manually, which often led to recording errors, delays in reporting, and difficulties in retrieving student payment data. To address these issues, a web-based information system was developed to assist the school administration in recording, reporting, and monitoring tuition payments more effectively and efficiently. The development method used in this study is the Model View Controller (MVC) approach, which separates the system’s view, logic, and database layers to simplify system management and maintenance. The final result of this research is a web-based tuition payment application that runs properly, provides convenience for school administrative staff in recording transactions, and enhances the accuracy and speed of the school’s financial administration process at SMA Swasta Manda Elu.